Burntown : a novel - McMahon, Jennifer, 1968- (Doubleday, 2017)
"Ashford, Vermont, might look like your typical sleepy New England college town, but to the shadowy residents who live among the remains of its abandoned mills and factories, it's known as "Burntown." Eva Sandeski, known as "Necco" on the street, has been a part of this underworld for years, ever since the night her father Miles drowned in a flood that left her and her mother Lily homeless. A respected professor, Miles was also an inventor of fantastic machines, including one so secret that the plans were said to have been stolen from Thomas Edison's workshop. According to Lily, it's this machine that got Miles murdered. Necco has always written off this claim as the fevered imaginings of a woman consumed by grief. But when Lily dies under mysterious circumstances, and Necco's boyfriend is murdered, she's convinced her mother was telling the truth. Now, on the run from the man called "Snake Eyes," Necco must rely on other Burntown outsiders to survive. There are the "fire eaters," mystical women living off the grid in a campsite on the river's edge, practicing a kind of soothsaying inspired by powerful herbs called "the devil's snuff"; there's Theo, a high school senior who is scrambling to repay the money she owes a dangerous man; and then there's Pru, the cafeteria lady with a secret life. As the lives of these misfits intersect, and as the killer from the Sandeski family's past draws ever closer, a story of edge-of-your-seat suspense begins to unfurl with classic Jennifer McMahon twists and surprises"--